2023
DOI: 10.1513/annalsats.202203-277oc
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the COVID-19 Pandemic on Author Sex and Manuscript Acceptance Rates among Pulmonary and Critical Care Journals

Abstract: Rationale The coronavirus disease (COVID-19) pandemic has negatively affected women more than men and may influence the publication of non–COVID-19 research. Objectives To evaluate whether the COVID-19 pandemic is associated with changes in manuscript acceptance rates among pulmonary/critical care journals and sex-based disparities in these rates. Methods We analyzed first, senior, and corresponding author sex (female vs. male, identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…These trends spark curiosity surrounding academic productivity during the early COVID-19 pandemic. The increased publication trend during this pandemic period is noteworthy, mirrored the 36% increase in all Journal of Perinatology submissions between study periods, and was reported similarly by other journals (20)(21)(22). This nding may be re ective of work prior to the pandemic as manuscript preparation is typically the culmination of months to years of preceding research.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These trends spark curiosity surrounding academic productivity during the early COVID-19 pandemic. The increased publication trend during this pandemic period is noteworthy, mirrored the 36% increase in all Journal of Perinatology submissions between study periods, and was reported similarly by other journals (20)(21)(22). This nding may be re ective of work prior to the pandemic as manuscript preparation is typically the culmination of months to years of preceding research.…”
Section: Discussionsupporting
confidence: 66%
“…However, many reports cite signi cant negative pandemic impact on both professional responsibilities and personal obligations that interfere with work; concerningly, these reports show greater negative effects on women (12,(16)(17)(18)24). Though we found no change in the gender proportions of authorship between pre-pandemic and pandemic periods for the Journal of Perinatology, the literature on this topic shows mixed results (20)(21)(22)(25)(26)(27). These trends warrant attention as the pandemic wears on and its true impact on academic work remains to be seen.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…found that the proportion of female first and senior authors stayed the same between 2008 and 2018. Another study investigated how COVID-19 impacted the authorship of critical care research and found no considerable difference in the proportion of female first and senior authors during the COVID-19 and post-COVID-19 eras [13].…”
Section: Trends In Gender Differencesmentioning
confidence: 99%
“…FIGURE 3: A forest plot showing gender differences in senior authorshipOR: odds ratio; CI: confidence interval; M-H: Mantel-Haenszel[11][12][13][14][15][16][17] …”
mentioning
confidence: 99%